Pengembangan media picto guru berbasis metode sariswara sebagai sarana berpikir kritis siswa kelas III SD Negeri Pingit Yogyakarta - Clara, Clara; Sari, Dyan Indah Purnama; Taryatman, Taryatman; Arief, Ardian (Universitas Sarjanawiyata Tamansiswa, 2025)
The objectives of this study are to: 1) explain how Picto Guru media, which is based on the Sariswara method, was developed as a tool to improve students' critical thinking abilities; 2) explain whether Picto Guru media, which is based on the Sariswara method, is feasible as a tool to support students' critical thinking; and 3) explain how students react to using Picto Guru media. The five steps of the ADDIE development model—analysis, design, development, implementation, and evaluation—are used in this study in conjunction with the Research and Development (R&D) technique. Six students participated in this study, which was carried out at SD Negeri Pingit Yogyakarta. This study employed questionnaires, interviews, and observation as data gathering methods. Questionnaires for media experts, material specialists, classroom teachers, and student answers were among the tools utilised. A Likert scale with percentage values was used in the data analysis method. The study's findings indicate that: 1) Picto Guru media has been developed through the phases of analysis, design, development, implementation, and evaluation; 2) the material expert's validation of the media yielded a 90% percentage score, the media expert's second validation yielded an 81.43% percentage score, and the classroom teacher's third validation yielded an 86.67% percentage score. Ultimately, the three validators' average score for Picto Guru media came out to 86.03%, which is in the